New truck vibrator for VSP surveys, extending the frequency bandwidth - Tulett, J.; Dean, Timothy; Armstrong, P.; Lane, D. (2013)
On land, the preferred seismic energy source for Vertical Seismic Profile (VSP) surveys is the seismic vibrator, a special vehicle mounted, mobile energy source.Seismic vibrators come in a variety of shapes and sizes, with truck-mounted vibrators the most common vehicle type during the early years of vibroseis surveys. Truck-mounted vibrators are particularly useful for VSP surveys because the vehicle can be driven directly to the well site, but over the years the surface seismic industry has converted to buggy vibrators due to the buggy's excellent mobility in off-road terrains. This has left a gap in development of truck-mounted vibrators. With petroleum exploration occurring in deeper wells, more complex sub-surface formations, and with steadily higher expectations for the results of VSP operations, there is a need for higher amplitude, and wider bandwidth seismic vibrators to provide critical geophysical information of petroleum reservoirs. In oilfield operations a key objective is reducing the safety risk during vibrator transport to and from the wellsite. To properly acquire a VSP survey the critical geophysical objectives are: • Improving seismic data quality • Widening the frequency bandwidth • Delivering consistent and repeatable sweeps (essential for 4D surveys) In this paper we describe how we met these challenges by developing two new VSP truck vibrators that offer a new level of safety, data quality and efficiency. The new truck vibrators for VSP surveys provide high output, wide bandwidth with extended low frequencies, low distortion data, together with purpose built carriers which improve safety and logistics for wellsite operations. The paper will provide actual borehole seismic data examples comparing a conventional VSP vibrator vs. the new extended bandwidth VSP vibrators. Copyright © (2013) by the Society of Petroleum Engineers.